Reduction of the residual stresses in cold expanded thick-walled cylinders by plastic compression; Defence Technology; Vol. 12, iss. 6 - Skvortsov V. F. Vladimir Fedorovich; Boznak A. O. Aleksey Olegovich; Kim A. B. Aleksey Bogovich; Arlyapov A. Yu. Aleksey Yurievich; Dmitriev A. I. Andrey Ivanovich (2016, 2016)
Title screen